A systematic comparison of bar-clips versus magnets - Brandao, Thais Bianca; Vechiato Filho, Aljomar Jose; Souza Batista, Victor Eduardo de [UNESP]; Querido de Oliveira, Maria Cecilia; Visser, Anita; Marques de Faria, Jose Carlos; Castro Junior, Gilberto de; Santos-Silva, Alan Roger (Elsevier B.V., 2017)
Statement of problem. Currently, which type of suprastructure is preferred when fabricating implant-retained craniofacial prostheses is unknown. Purpose. The purpose of this systematic review was to identify the best retention system (bar-clips versus magnets) for implant-retained craniofacial prostheses. Material and methods. This systematic review was conducted and reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. A systematic search of Medline/PubMed and Web of Science databases for clinical trials was conducted on implant-retained craniofacial prostheses published between 2005 and 2015. English -language studies that directly compared different types of retention systems or presented information on implant survival, periimplant soft tissue reactions, and prosthetic complications were included. Nonclinical studies were excluded to eliminate bias. Results. A total to 173 studies were identified, of which 10 satisfied the inclusion criteria. In total, 492 participants were included in these studies. Four selected studies displayed detailed information with regard to the number of implant failures according to the retention system. As reported, 29 (18.2%) of 159 implants with magnets failed, whereas 25 (31.6%) of 79 implants with bars failed. Overall auricular superstructures showed the highest survival (99.08%). In addition, 55.4% of all participants in the selected studies showed grade 0 of periimplant soft tissue reactions. Conclusions. A systematic search for clinical studies resulted in few studies with a short-term follow-up and small number of participants. The limited data collected indicated that magnets show fewer complications than bar superstructures; however, no hard conclusions could be drawn. Further research, preferably in the form of clinical trials, is needed to validate these findings.